Receptor-specific mechanisms regulate phosphorylation of AKT at Ser473: role of RICTOR in β1 integrin-mediated cell survival. - Anjum Riaz; Kathrin Stephanie Zeller; Staffan Johansson (PLoS ONE, 2012)
A tight control over AKT/PKB activation is essential for cells, and they realise this in part by regulating the phosphorylation of Ser473 in the "hydrophobic motif" of the AKT carboxy-terminal region. The RICTOR-mTOR complex (TORC2) is a major kinase for AKT Ser473 phosphorylation after stimulation by several growth factors, in a reaction proposed to require p21-activated kinase (PAK) as a scaffold. However, other kinases may catalyse this reaction in stimuli-specific manners. Here we characterised the requirement of RICTOR, ILK, and PAK for AKT Ser473 phosphorylation downstream of selected family members of integrins, G protein-coupled receptors, and tyrosine-kinase receptors and analysed the importance of this phosphorylation site for adhesion-mediated survival. siRNA-mediated knockdown in HeLa and MCF7 cells showed that RICTOR-mTOR was required for phosphorylation of AKT Ser473, and for efficient phosphorylation of the downstream AKT targets FOXO1 Thr24 and BAD Ser136, in response to β1 integrin-stimulation. ILK and PAK1/2 were dispensable for these reactions. RICTOR knockdown increased the number of apoptotic MCF7 cells on β1 integrin ligands up to 2-fold after 24 h in serum-free conditions. β1 integrin-stimulation induced phosphorylation of both AKT1 and AKT2 but markedly preferred AKT2. RICTOR-mTOR was required also for LPA-induced AKT Ser473 phosphorylation in MCF7 cells, but, interestingly, not in HeLa cells. PAK was needed for the AKT Ser473 phosphorylation in response to LPA and PDGF, but not to EGF. These results demonstrate that different receptors utilise different enzyme complexes to phosphorylate AKT at Ser473, and that AKT Ser473 phosphorylation significantly contributes to β1 integrin-mediated anchorage-dependent survival of cells.